Ultra-wide band microwave filter utilizing quarter-wavelength short-circuited stubs - Mohammad Shahrazel, Razalli; Alyani, Ismail; Mohd Adzir, Mahdi; Mohd Nizar, Hamidon (Wiley Periodicals, 2009)
Link to publisher's homepage at http://www3.interscience.wiley.com